Sublethal effects of zinc oxide nanoparticles on male reproductive cells. (September 2016) - Liu, Qian; Xu, Cheng; Ji, Guixiang; Liu, Hui; Mo, Yiqun; Tollerud, David J.; Gu, Aihua; Zhang, Qunwei
Abstract: Environmental exposure to nanomaterials is inevitable as nanomaterials become part of our daily life, and as a result, nanotoxicity research is gaining attention. Most investigators focused on the effects of zinc oxide nanoparticles (ZnO NPs) on human health, while limited information was available on the male reproductive system. Herein, mouse Sertoli cell line (TM-4) and spermatocyte cell line (GC2-spd) were used as in vitro models to explore the reproductive effects of ZnO NPs at sublethal dose and its underlying mechanisms. Cells were treated with different concentrations of ZnO NPs. By cell viability assay, a dose of 8 μg/mL was found as a sublethal dose and increased the ROS levels in both cells. The decreased glutathione level and increased MDA level were also found in ZnO NPs treated group. In TM4 cells, the expressions of BTB proteins (ZO-1, occludin, claudin-5, and connexin-43) were lower in the ZnO NPs group. The increased cell permeability and increased TNF-α secretion were also observed in ZnO NPs group. In GC2-spd cells, S phase arrest and DNA damage occurred in ZnO NPs group, which could be partially rescued by NAC. Our findings demonstrated that exposure to ZnO NPs induced ROS generation, caused DNA damage of germ cells, and down-regulated the expression of BTB proteins in Sertoli cells which could compromise the integrity of the blood-testis barrier. All these contributed to the male reproductive cytotoxic effects of ZnO NPs that could be partially rescued by anti-oxidants. Graphical abstract: Schematic summary of potential biological hazards and mechanism of ZnO NPs impact on the male reproductive system using TM-4 cells and GC2-spd cells as in vitro evaluation models. Highlights: Sertoli (TM-4) and spermatocyte (GC2-spd) cell lines were used as in vitro models. A sublethal dose of 8 μg/mL ZnO NPs induced oxidative stress in both cells lines. Exposure to ZnO NPs down-regulated the expression of the blood-testis barrier proteins in Sertoli cells. Exposure to ZnO NPs caused DNA damage in germ cells. All these could be partially rescued by the antioxidants.